First record of Pontaralia beklemichevi Mack-Fira, 1968 (Platyhelminthes: Rhabdocoela: Kalyptorhynchia) from the Russian Federation - Tokinova, Rimma P.; Berdnik, Sergey V.; Ratushnyak, Anna A. (Zootaxa, 2011)
This is the first record of Pontaralia beklemichevi Mack-Fira, 1968 since its original description from Romania. Found in Lake Middle Kaban (Kazan, the Middle Volga basin), this species is new for Russian fauna. It is a relict of Ponto-Aral-Caspian that has recently invaded the Middle Volga basin. In the morphology of the male reproductive system, larger cirrus spines were noted in comparison with the original description.